An Analysis of Ontology Metaphore in the Legend of Putri Hijau Book - Aisyah, Yenni (Al'Adzkiya Journal, 2022)
This study discusses the conceptual metaphor and described metaphorical terminology as the result of a combination of two Greek words; meta (above) and pherein (redirect or move). This research used the descriptive qualitative method. The data was taken from the text of the book. Based on the result of this research on the ontology metaphor in The Legend of Putri Hijau book, it was found totally of 15 dialogs. There are The Legend of Putri Hijau 3, The Legend of Toba Lake 4, The Legend of Lau Kawar Lake 5, and The Legend of Sigale-gale Statue 3.